2001
DOI: 10.1175/1520-0469(2001)058<1288:ltootd>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Observations of the Dynamics of the Continental Planetary Boundary Layer

Abstract: Time series of mixed layer depth, z i , and stable boundary layer height from March through October of 1998 are derived from a 915-MHz boundary layer profiling radar and CO 2 mixing ratio measured from a 447-m tower in northern Wisconsin. Mixed layer depths from the profiler are in good agreement with radiosonde measurements. Maximum z i occurs in May, coincident with the maximum daytime surface sensible heat flux. Incoming radiation is higher in June and July, but a greater proportion is converted to latent h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
148
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(154 citation statements)
references
References 34 publications
6
148
0
Order By: Relevance
“…The numerical experiments that do not consider subsidence overestimate the observed z 1 by less than 200 m. Long-term observations of the boundary layer show the importance of considering subsidence to obtain realistic approximations (Yi et al, 2001;Pietersen et al, 2014).…”
Section: Boundary-layer Depth Temporal Evolutionmentioning
confidence: 86%
See 2 more Smart Citations
“…The numerical experiments that do not consider subsidence overestimate the observed z 1 by less than 200 m. Long-term observations of the boundary layer show the importance of considering subsidence to obtain realistic approximations (Yi et al, 2001;Pietersen et al, 2014).…”
Section: Boundary-layer Depth Temporal Evolutionmentioning
confidence: 86%
“…We obtain the value of subsidence to be included in DALES and MLM numerical experiments, following Yi et al (2001), by analyzing the observed vertical profile of the potential temperature at 01:30 and 07:30 UTC on 1 July 2011 (see Fig. 2).…”
Section: Numerical Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results from clear days in winter and summer are mapped in Figure 10 for two example days. The mixing layer height is primarily driven by variation in the vertical flux of energy and momentum caused by the balance between the heating of the earth's surface by incoming solar radiation and radiative cooling of the surface [27][28][29]. Accordingly, as Figure 10 shows, the MH is lower in the winter and relatively higher in the summer, demonstrating that net radiation is the main factor driving the development of the PBL.…”
Section: Mh Spatial and Temporal Patternsmentioning
confidence: 97%
“…The main processes responsible for the formation of SBL are (1) cooling of the surface due to a negative radiation budget (Sun et al, 2003), (2) warm-air advection over a cold surface (Vihma et al, 2003), and (3) subsidence (Yi et al, 2001). A variety of subgrid-scale processes may occur in a SBL, e.g.…”
Section: Introductionmentioning
confidence: 99%